2009
DOI: 10.1186/1471-2407-9-84
|View full text |Cite
|
Sign up to set email alerts
|

Breast cancer epidemiology according to recognized breast cancer risk factors in the Prostate, Lung, Colorectal and Ovarian (PLCO) Cancer Screening Trial Cohort

Abstract: BackgroundMultidisciplinary attempts to understand the etiology of breast cancer are expanding to increasingly include new potential markers of disease risk. Those efforts may have maximal scientific and practical influence if new findings are placed in context of the well-understood lifestyle and reproductive risk factors or existing risk prediction models for breast cancer. We therefore evaluated known risk factors for breast cancer in a cancer screening trial that does not have breast cancer as a study endp… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

4
69
1
10

Year Published

2011
2011
2018
2018

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 130 publications
(84 citation statements)
references
References 37 publications
4
69
1
10
Order By: Relevance
“…These potential confounders were based on register availability, a review of the literature, and decided upon a priori (40,41). Data were virtually complete within the time frame of available data for all variables except for female first degree relatives (5% missing).…”
Section: Covariatesmentioning
confidence: 99%
“…These potential confounders were based on register availability, a review of the literature, and decided upon a priori (40,41). Data were virtually complete within the time frame of available data for all variables except for female first degree relatives (5% missing).…”
Section: Covariatesmentioning
confidence: 99%
“…Breast cancer has known risk factors such as the cellular aging, family history, alcohol consumption (2), overweight (3), sedentary lifestyle, and high breast tissue density (4). Other risk factors are related to women's reproductive life, which leads to increased endogenous estrogen levels, as the later age at first childbirth, early menarche, and late menopause (1,3). Some studies indicated that sun exposure and vitamin D levels are inversely proportional to the risk of developing breast cancer (5,6).…”
Section: Introductionmentioning
confidence: 99%
“…Breastfeeding has a protective effect. [3,5] The other important risk factors for the development of breast cancer are gender, age, and genetics. As women can do nothing about these risks, regular screening is recommended to allow early detection and thus prevent death from breast cancer.…”
Section: Introductionmentioning
confidence: 99%